Robust circulation changes in the tropics under a warming climate: a topical review - Thomas, Tresa Mary; Bala, Govindasamy (Frontiers in Climate, 2025)
Tropical monsoons are crucial atmospheric phenomena that impact more than two-thirds of the global population. Numerous previous studies have investigated changes in tropical circulation under climate change for individual ocean basins. In this review, we synthesize the robust changes in tropical atmospheric circulations and precipitation under a warming climate using CMIP6 data for illustration. Sea surface temperature, precipitation, and cloud cover are enhanced over the central and eastern Pacific, similar to El-Niño. In the Indian Ocean basin, the sea surface warming pattern is similar to the positive Indian Ocean Dipole phase, with low-level easterly anomalies in the central tropical Indian Ocean, which diverge into two anticyclones off the east coast of Africa. In the Atlantic, a larger increase in sea surface temperature is simulated along the eastern equatorial Atlantic, like an east Atlantic El-Niño condition. An increase in summer monsoon precipitation over South Asia and a decrease over North and South America, the Maritime continent, and Southern Africa are simulated. In the Northern African monsoon region, an east–west asymmetry is projected with a decrease in rainfall in the west and an increase in the east. The interconnection between the identified robust changes in circulation and precipitation over the three oceanic basins under a warming climate has been explored via earlier studies and model simulations. This review provides a holistic picture of regional tropical circulation and precipitation changes under a warming climate.